Compassion fatigue in pediatric nephrology—The cost of caring - Goldberg, Aviva M. (Frontiers in Pediatrics, 2022)
Compassion fatigue is the result of repeated vicarious trauma from caring for those who have suffered. Although not well-researched in pediatric nephrology to date, there is reason to believe that it is a real and sustained threat to the pediatric nephrology workforce. Interventions aimed at individuals, the profession, and the organizations in which pediatric nephrologists work can create spaces to discuss and ameliorate compassion fatigue. This will result in better care for patients, more stable pediatric nephrology divisions and a stronger, more resilient pediatric nephrology workforce.